Proceedings of the 19th ACM Conference on Computer-Supported Cooperative Work &Amp; Social Computing 2016
DOI: 10.1145/2818048.2820012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exposure to Social Annotation on Online Informed Consent Beliefs and Behavior

Abstract: In this study we explore the impact of exposure to social annotation, embedded in online consent forms, on individuals' beliefs and decisions in the context of informed consent. In this controlled between-subjects experiment, participants were presented with an online consent form for a personal genomics study. Individuals were randomly assigned to either a social annotation condition that exposed them to previous users' comments on-screen, or to a traditional consent form without social input. We compared par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Among the randomized controlled trials, only 3 studies [ 25 - 27 ] received a quality score of 3. Quality scores of 2 and 1 were provided to 1 study [ 28 ] and 6 studies [ 29 - 34 ], respectively. The qualitative studies ranged from satisfying 80% or more of the quality criteria (6 studies) [ 35 - 40 ] to satisfying 50% to 60% of the quality criteria (3 studies) [ 41 - 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the randomized controlled trials, only 3 studies [ 25 - 27 ] received a quality score of 3. Quality scores of 2 and 1 were provided to 1 study [ 28 ] and 6 studies [ 29 - 34 ], respectively. The qualitative studies ranged from satisfying 80% or more of the quality criteria (6 studies) [ 35 - 40 ] to satisfying 50% to 60% of the quality criteria (3 studies) [ 41 - 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The usefulness of additional content elements such as definitions was articulated in a focus group involving research participants who were older adults [ 45 ]. Moreover, exposing research participants to social annotation, such as comments generated by end users on several aspects of the electronic informed consent form, was considered important to feel adequately informed [ 29 ]. However, the emotional force communicated in social annotations has an influence on research participants’ perceptions with regard to information given in electronic informed consent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that this information could impact user decisions, but only if the cues were sufficiently strong. Balestra et al [5] studied the impact of exposure to social annotations on privacy consent for a genomics application. These annotations had the general effect of making users feel more informed, but also less confident in their understanding of the application and less trusting in the institution soliciting the consent.…”
Section: :5mentioning
confidence: 99%
“…In a previous study [ 6 ], we hypothesized that incorporating user-generated social annotations into online consent forms with complex content would allow individuals to benefit and learn from others’ perspectives, knowledge, and ideas by encouraging discussion and helping to focus attention on the issues that users find important. We designed such a tool and evaluated it compared to a control condition of an online consent form with no social annotation.…”
Section: Introductionmentioning
confidence: 99%